2021
DOI: 10.3390/catal11121532
|View full text |Cite
|
Sign up to set email alerts
|

Hollow TiO2 Microsphere/Graphene Composite Photocatalyst for CO2 Photoreduction

Abstract: In an attempt to improve the photocatalytic activity of anatase TiO2, we developed a composite photocatalyst composed of hollow TiO2 microspheres (hTS) and graphene. The hTS were prepared through a two-step hydrothermal process, where SiO2 microspheres with desirable diameters of 100–400 nm were used as sacrificial templates. Accordingly, the effect of the hTS cavity size on the activity of the catalyst in wet CO2 photoreduction (CO2PR) was studied. Furthermore, it was established that the hydrothermal pH valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…Lo et al compared the photocatalytic activities of TiO 2 HoNRs with cavity sizes ranging from 100 to 400 nm and found that the optimal cavity size for photocatalytic activity was 200 nm. [102] Even, Hsu et al stated that photocatalytic efficiency enhances with the increase in cavity size due to the void effect even after excluding the influence of specific surface area. [48] This difference is also reflected in the range of light absorption, where photocatalysts with larger cavity sizes exhibit smaller bandgaps, indicating a broader light absorption capabilities.…”
Section: Cavitymentioning
confidence: 99%
See 1 more Smart Citation
“…Lo et al compared the photocatalytic activities of TiO 2 HoNRs with cavity sizes ranging from 100 to 400 nm and found that the optimal cavity size for photocatalytic activity was 200 nm. [102] Even, Hsu et al stated that photocatalytic efficiency enhances with the increase in cavity size due to the void effect even after excluding the influence of specific surface area. [48] This difference is also reflected in the range of light absorption, where photocatalysts with larger cavity sizes exhibit smaller bandgaps, indicating a broader light absorption capabilities.…”
Section: Cavitymentioning
confidence: 99%
“…compared the photocatalytic activities of TiO 2 HoNRs with cavity sizes ranging from 100 to 400 nm and found that the optimal cavity size for photocatalytic activity was 200 nm. [ 102 ] Even, Hsu et al. stated that photocatalytic efficiency enhances with the increase in cavity size due to the void effect even after excluding the influence of specific surface area.…”
Section: Structure–performance Relationship Of Honrs To Photocatalysismentioning
confidence: 99%
“…Among other detrimental factors, global climate change is largely caused by the increase in atmospheric CO 2 emissions originating from the burning of fossil fuels for energy production, deforestation, and industrial processes. Therefore, the photoreduction of CO 2 (CO 2 PR) in high-added-value products has emerged as an environmental alternative to mitigate the greenhouse effect and energy problems through CO 2 capture and air purification [5][6][7]. Inspired by natural photosynthesis [8], the scientific community has developed many biomimetic approaches to design photocatalytic systems capable of converting CO 2 molecules into valuable fuels (CO, HCHO, HCOOH, CH 3 OH and CH 4 ) under visible light irradiation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…By the combination of CeO 2 or MnO x with phase-pure M1 catalysts, composite catalysts markedly enhance the catalytic performance for the ODHE process [9,44,45,49], which provides a possibility and preliminary verification on adding cheaper promoters to increase the catalytic activities of MoVNbTeO x catalysts. TiO 2 as an effective promoter/catalyst has been widely used in catalytic processes [50][51][52]. Holmberg et al [53] used TiO 2 as a diluter to study the catalytic performance for propane ammoxidation.…”
Section: Introductionmentioning
confidence: 99%